HABITAT QUALITY MUD CRAB (Scylla serrata) IN MANGROVE ECOSYSTEM OF BINTAN BAY, BINTAN DISTRIC, RIAU ISLANDS - M. Tahmid; Achmad Fahrudin; Yusli Wardiatno (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Mud crab (Scylla serrata) is one of small scale fisheries commodity that have high economic value and typically associated with good mangrove ecosystem. A habitat degradation will cause a serious impact on the existence of mud crab population. The puropse of this study was to assess the ecological quality of mud crab habitat condition on Bintan Bay’s mangrove ecosystem. Ecological data collection was conducted by using plots line transect for mangrove and the mud carb data collection by using fishermen catch (fisher based survey). The results showed the value of habitat quality index (HQI) of mud crab (Scylla serrata) ranged from 52-82 which mean in the “moderate” category (index value 43-66) and